PENGARUH PERILAKU KELUARGA TERHADAP PENCEGAHAN MALARIA DI DESA MBATAKAPIDU KABUPATEN SUMBA TIMUR - Umbu Putal Abselian; Umbu Nggiku Njakatara; Melkisedek Landi (Bajang Institute, 2025)
Introduction. Malaria is one of the public health problems in Indonesia, with a frequent increase in the number of cases and a wider spread. According to data from the World Health Organization (WHO), there were 219 million malaria cases worldwide in 2019. The spread of malaria is also influenced by the community’s low level of knowledge about the causes of transmission; knowledge of malaria prevention significantly affects its spread. Many people do not understand that malaria can be transmitted from parent to child. They believe that malaria is transmitted through shared blood or heredity.Objective.To determine the influence of family behavior on the prevention of malaria in Mbatakapidu Village, East Sumba Regency. Method. This research is a correlational study using a purposive sampling technique with 30 respondents. The instrument used was a questionnaire. Results. The results showed that in Mbatakapidu Village, 17 people (57%) had good behavior regarding malaria prevention, 11 people (37%) had moderate behavior, and 2 people (6%) had poor behavior. Conclusion. Based on this study, most of the families in Mbatakapidu Village demonstrated good behavior in preventing malaria. Recommendation.It is recommended that Waingapu Health Center continue providing malaria education by involving healthcare workers and the community.